Efficient treatment of breast cancer xenografts with multifunctionalized iron oxide nanoparticles combining magnetic hyperthermia and anti-cancer drug delivery - VOLKOV, YURI (My University, 2015)
Introduction Tumor cells can effectively be killed by heat, e.g. by using magnetic hyperthermia. The main challenge in the field, however, is the generation of therapeutic temperatures selectively in the whole tumor region. We aimed to improve magnetic hyperthermia of breast cancer by using innovative nanoparticles which display a high heating potential and are functionalized with a cell internalization and a chemotherapeutic agent to increase cell death. Methods The superparamagnetic iron oxide nanoparticles (MF66) were electrostatically functionalized with either Nucant multivalent pseudopeptide (N6L; MF66-N6L), doxorubicin (DOX; MF66-DOX) or both (MF66-N6LDOX). Their cytotoxic potential was assessed in a breast adenocarcinoma cell line MDA-MB-231. Therapeutic efficacy was analyzed on subcutaneous MDA-MB-231 tumor bearing female athymic nude mice. Results All nanoparticle variants showed an excellent heating potential around 500 W/g Fe in the alternating magnetic field (AMF, conditions: H = 15.4 kA/m, f = 435 kHz). We could show a gradual inter- and intracellular release of the ligands, and nanoparticle uptake in cells was increased by the N6L functionalization. MF66-DOX and MF66-N6LDOX in combination with hyperthermia were more cytotoxic to breast cancer cells than the respective free ligands. We observed a substantial tumor growth inhibition (to 40% of the initial tumor volume, complete tumor regression in many cases) after intratumoral injection of the nanoparticles in vivo. The proliferative activity of the remaining tumor tissue was distinctly reduced. Conclusion The therapeutic effects of breast cancer magnetic hyperthermia could be strongly enhanced by the combination of MF66 functionalized with N6L and DOX and magnetic hyperthermia. Our approach combines two ways of tumor cell killing (magnetic hyperthermia and chemotherapy) and represents a straightforward strategy for translation into the clinical practice when injecting nanoparticles intratumorally.
PUBLISHED
Keywords: doxorubicin; iron oxide nanoparticle; nanoparticle; pseudopeptide; succimer; unclassified drug; doxorubicin; iron oxide nanoparticle; nanoparticle; pseudopeptide; succimer; unclassified drug